2016
DOI: 10.1155/2016/8917578
|View full text |Cite
|
Sign up to set email alerts
|

Update on RAAS Modulation for the Treatment of Diabetic Cardiovascular Disease

Abstract: Since the advent of insulin, the improvements in diabetes detection and the therapies to treat hyperglycemia have reduced the mortality of acute metabolic emergencies, such that today chronic complications are the major cause of morbidity and mortality among diabetic patients. More than half of the mortality that is seen in the diabetic population can be ascribed to cardiovascular disease (CVD), which includes not only myocardial infarction due to premature atherosclerosis but also diabetic cardiomyopathy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 235 publications
(192 reference statements)
2
82
0
2
Order By: Relevance
“…Prior studies suggested that angiotensin-converting enzyme 2 (ACE2)-binding capacity is strongly associated with coronavirus infectivity and disease severity. ACE2 may be differentially upregulated by ACEi, ARB, and aldosterone antagonists [12][13][14]. It is postulated that the expression of ACE2 may be increased with the use of ACEi, ARB, and aldosterone antagonists, particularly in diabetic patients, and therefore it has been suggested that increased expression of ACE2 may facilitate infection by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggested that angiotensin-converting enzyme 2 (ACE2)-binding capacity is strongly associated with coronavirus infectivity and disease severity. ACE2 may be differentially upregulated by ACEi, ARB, and aldosterone antagonists [12][13][14]. It is postulated that the expression of ACE2 may be increased with the use of ACEi, ARB, and aldosterone antagonists, particularly in diabetic patients, and therefore it has been suggested that increased expression of ACE2 may facilitate infection by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin‐II (Ang‐II) is produced by cardiac myocytes and fibroblasts in response to hemodynamic stresses, and Ang‐II‐dependent and Ang‐II‐independent cascades are activated in hypertension, heart failure (HF), and other conditions . The mineralocorticoid aldosterone is a key component of the renin–angiotensin–aldosterone system (RAAS), produced by aldosterone synthase .…”
Section: Discussionmentioning
confidence: 99%
“…The RAAS contributes to the etiology of CVD and diabetes . In patients with type I diabetes, plasma levels of renin, Ang‐II, and aldosterone are elevated .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular events account for two‐thirds of the mortality in patients with diabetes (Boudina & Abel, 2007). Diabetic cardiomyopathy (DCM) is a major cardiovascular complication (Bernardi, Michelli, Zuolo, Candido & Fabris, 2016). DCM is defined as structural and functional myocardial impairments in diabetic patients without coronary artery disease or hypertension.…”
Section: Introductionmentioning
confidence: 99%